Enhancing the Knowledge-Governance Interface: Coasts, Climate and Collaboration. - Clarke, Beverley; Stocker, Laura; Coffey, Brian; Leith, Peat; Harvey, Nicholas; Baldwin, Claudia; Baxter, Tom; Bruekers, Aldegonda; Danese Galano, Chiara; Good, Meg; Hofmeester, Carolyn; Freitas, Debora; et al. (Elsevier, 2013)
Conventional systems of government have not been very successful in resolving coastal management problems. This lack of progress is partially attributable to inadequate representation in governance processes of the variety of knowledges present on the coast. In particular there has been a struggle to engage effectively with climate science and its implications. There has also been a broader failure to capture the complexity of voices, interests, values, and discourses of coastal users. We argue here that coastal governance challenges are not likely to be resolved by singular solutions; rather, interaction and collaboration will generate improvements. We suggest that a co-requisite for progress in coastal management is the development of institutions and processes that enable different knowledges to have a bearing on governance processes. This paper examines a selection of the many opportunities available to broaden and enhance the use of knowledge in decision-making for the coast. A description is provided of emerging elements of coastal governance from an Australian perspective, together with new types of institutions, processes, tools and techniques that may help to achieve an improved coastal knowledge –governance interaction.